Decreased Memory-Related Regional Cerebral Perfusion in Severe Obstructive Sleep Apnea with a Mild Cognitive Impairment During Wakefulness - Yan X; Liu W; Li D; Huang Q; Wu J; Zhang Q (Nature and Science of Sleep)
Xiangbo Yan,1,2 Wanqing Liu,3 Danyang Li,1 Qiang Huang,1 Jianlin Wu,1 Qing Zhang1 1Imaging Department, Affiliated Zhongshan Hospital Dalian University, Dalian, People’s Republic of China; 2Faculty of Medicine, Dalian University of Technology, Dalian, People’s Republic of China; 3Department of Radiology, West China Second University Hospital, Sichuan University, Chengdu, People’s Republic of ChinaCorrespondence: Qing Zhang, Imaging Department, Affiliated Zhongshan Hospital, Dalian University, Dalian, 116001, People’s Republic of China, Tel +86 15566978288, Email zhangqingsmile@163.comPurpose: Previous studies have found that obstructive sleep apnea (OSA) can induce cognitive impairment (CI). However, the exact mechanisms of CI development in patients with OSA remains unclear. We investigated the neuropathological basis of CI development by examining changes in cerebral blood perfusion.Patients and Methods: Thirty-five patients with untreated OSA (15 with CI and 20 without CI [NCI]) and 15 good sleepers (GS) diagnosed using polysomnography were recruited. All participants underwent resting state brain scans in a Siemens 3.0 Tesla magnetic resonance imaging scanner with a pulsed arterial spin labeling sequence and completed a battery of neuropsychological tests.Results: Compared to the regional cerebral blood flow (rCBF) values in the GS group, both the CI and NCI groups exhibited lower rCBF values in the bilateral inferior temporal, left lingual, and right medial and paracingulate gyri, as well as higher rCBF values in the bilateral middle frontal gyrus (p < 0.05 in all cases). Compared to the rCBF values in the NCI group, the CI group had lower rCBF values in the bilateral inferior temporal and left lingual gyri, and higher rCBF values in the right rectus and right middle orbital frontal gyri (p < 0.05 in all cases). In the CI group, rCBF values in the bilateral inferior temporal (right, p = 0.025; left, p = 0.005) and left lingual gyri (p = 0.018) were positively associated with the delayed memory scores, and rCBF values in the left inferior temporal gyrus positively correlated with the attention scores (p = 0.011).Conclusion: Regions with abnormal perfusion in the NCI and CI groups were mostly memory-related. Blood perfusion in the bilateral inferior temporal and left lingual gyri decreased in the following order: GS > OSA-NCI > OSA-CI. These findings provide blood perfusion-level insights into the neuropathological basis of OSA-CI development.Keywords: Obstructive sleep apnea, cognitive impairment, cerebral blood flow, memory function, arterial spin labeling